Perspectivism in “before the world didn't exist” - Vasconcelos Moraes, Jéssika (2022)
Our purpose in this paper is discush, based on the literature masterpiece Before the World didn't exist (2019) and the Theory of Perspectivism of Viveiros de Castro. The storytelling shows the Desana mythology, since the beginning of Universe, pointing up importants aspects to the culture. We search to comprehend the relation between the transmutations suffered by the characters, under the point of view of Perspectivism as a phenomenon that defends that the body as involucre, possible of modification. For that, this search approaches structurals and thematic aspects of the masterpiece. We selected for tales to analyse: “The history of Gãipayã and the origin of the pupunha”, “Manioc origins history”, “Three stories of Buhtari Gõãmũ, the lazy spirit” and “The walkings by the world of Umukomahsü Boreka”. We noted that the changes suffered by characters in the tales happened by diferents reasons. By the way, we related the analyzed facts with the perspectivism light because, although the change occurs in differents way, this theory comprehend the transition between species, the characters intrinsec shamanism and the knowledge that they use to modify your exterior form, in occupation of a animal body.